2020
DOI: 10.3390/rs12101554
|View full text |Cite
|
Sign up to set email alerts
|

Tree Species (Genera) Identification with GF-1 Time-Series in A Forested Landscape, Northeast China

Abstract: Forests are the most important component of terrestrial ecosystem; the accurate mapping of tree species is helpful for the management of forestry resources. Moderate- and high-resolution multispectral images have been commonly utilized to identify regional tree species in forest ecosystem, but the accuracy of recognition is still unsatisfactory. To enhance the forest mapping accuracy, this study integrated the land surface phenological metrics and text features of forest canopy on tree species identification b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 99 publications
(101 reference statements)
0
4
0
Order By: Relevance
“…As a medium-resolution satellite, Gaofen-1 was launched in 2013, and its data have been freely available since 2019. Scholars used Gaofen-1 and Sentinel-1 data to conduct research in various fields [52,53]. However, it was unknown whether the performance of Gaofen-1 and Sentinel-1 was appropriate for coniferous forest identification.…”
Section: The Performance Of the Proposed Methodological Frameworkmentioning
confidence: 99%
“…As a medium-resolution satellite, Gaofen-1 was launched in 2013, and its data have been freely available since 2019. Scholars used Gaofen-1 and Sentinel-1 data to conduct research in various fields [52,53]. However, it was unknown whether the performance of Gaofen-1 and Sentinel-1 was appropriate for coniferous forest identification.…”
Section: The Performance Of the Proposed Methodological Frameworkmentioning
confidence: 99%
“…For example, Liu et al [42] demonstrated that the anthocyanin content index and photochemical reflectance index were the most important HS features for the identification of TS in the spring season when they mapped urban tree species by integrated airborne HS image and LiDAR data. Xu et al [131] reported that the integration of time-series GF-1 NDVI images, vegetation growth status, and feature of canopy information simultaneously will be beneficial to mapping TS at a landscape scale.…”
Section: Feature Types and Selectionmentioning
confidence: 99%
“…The swath width of the GF-1 WFV can reach up to 800 km when the four wide-width cameras are combined [8]. Currently, the image of the GF-1 satellite has been widely used in the fields of forestry [9,10], agriculture [11][12][13], and ecological environment [14,15], making up to a certain extent for the shortcomings in the application of high-resolution satellite data in China.…”
Section: Introductionmentioning
confidence: 99%